2013
DOI: 10.1128/cmr.00074-12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and Implications of Mortality Associated with Acute Plasmodium vivax Malaria

Abstract: SUMMARYVivax malaria threatens patients despite relatively low-grade parasitemias in peripheral blood. The tenet of death as a rare outcome, derived from antiquated and flawed clinical classifications, disregarded key clinical evidence, including (i) high rates of mortality in neurosyphilis patients treated with vivax malaria; (ii) significant mortality from zones of endemicity; and (iii) the physiological threat inherent in repeated, very severe paroxysms in any patient, healthy or otherwise. The very well-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
314
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(339 citation statements)
references
References 146 publications
(114 reference statements)
5
314
2
6
Order By: Relevance
“…Primaquine, 8-aminoquinoline" has remained the only drug to resolve the latent phase of P. vivax in the liver (2,9,12). Primaquine can lead to deadly hemolysis in patients with glucose 6 phosphate dehydrogenase (G6PD) deficiency (2).…”
Section: Discussionmentioning
confidence: 99%
“…Primaquine, 8-aminoquinoline" has remained the only drug to resolve the latent phase of P. vivax in the liver (2,9,12). Primaquine can lead to deadly hemolysis in patients with glucose 6 phosphate dehydrogenase (G6PD) deficiency (2).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium vivax is not generally regarded as sufficiently virulent to cause death. Notwithstanding this benign reputation, over the last two to three decades, there have been multiple case studies of fatal vivax malaria (10,11) More recently, hospital and outpatient surveillance systems have shown that P. vivax-associated mortality may be occurring with greater frequency than previously thought or reported (12,13) In the present study, the most common age group amongst study population was 21 to 30 years (48%) followed by 41 to 50 years (17.3%) and 31 to 40 years (14.7%). This is in accordance to study conducted by Dilip R Patil et al, (14) in which also higher incidence of vivax malaria was seen in the age group of 21 to 30 (23.53%).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium falciparum is the most common (64%) cause of malaria in Ethiopia while P. vivax accounts for the remaining cases (34%) [3]. Plasmodium falciparum causes the most severe form of malaria, however, contrary to popular belief, P. vivax can also cause severe malaria and even death [5] and Ethiopia is home to the second highest number of cases [12% (n ~1020)] and mortality [12% (n ~372)] due to P. vivax (next only to India) in the world [2]. Malaria due to P. vivax and P. ovale are also characterized by relapses [6].…”
Section: Introductionmentioning
confidence: 99%